FAKTOR HAMBATAN DALAM PENGADAAN BARANG/JASA ELEKTRONIK DI DPRKPP KABUPATEN NGANJUK - Anggitasari, Inge (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2026)
E-procurement, also known as an electronic system for the procurement of goods and services, is a mechanism for acquiring goods and services that utilizes the latest developments in the field of information and communication technology to create a workflow that is more accessible, accountable, efficient, and effective. In practice, several obstacles are still often encountered, including in local government institutions, such as the Office handling Housing, Settlement Areas, and Land Affairs in Nganjuk Regency. This study aims to map the barrier elements in the e-procurement implementation process at the institution, while also formulating strategic steps that can be applied to mitigate the impact of these obstacles. To identify the most dominant barrier factors, this study analyzed the data using the relative importance index (RII) and confidence interval methods. The research results indicate that habitual practices in service provision and weak communication are the main barriers to the implementation of e-procurement in the relevant department. To minimize the impact of these two factors, it is necessary to increase the capacity of the human resources involved, as well as develop more adequate facilities, infrastructure, and technology to support the sustainability of the e-procurement system. Abstrak E-procurement, juga dikenal sebagai sistem elektronik untuk pengadaan barang dan jasa merupakan sebuah mekanisme perolehan barang dan jasa yang mendayagunakan perkembangan mutakhir dalam ranah teknologi informasi dan komunikasi guna mewujudkan suatu alur kerja yang lebih aksesibel, akuntabel, berdaya guna, dan efektif. Dalam praktiknya, sejumlah kendala masih sering dijumpai, termasuk pada lembaga pada tatanan pemerintahan lokal, sebagai contoh, Dinas yang menangani urusan Perumahan, Kawasan Permukiman, dan Pertanahan di Kabupaten Nganjuk. Kajian ini bertujuan untuk memetakan elemen-elemen penghalang pada proses implementasi e-procurement pada instansi tersebut, sekaligus merumuskan langkah-langkah strategis yang dapat diterapkan untuk mengurangi dampak dari hambatan tersebut. Untuk mengidentifikasi faktor hambatan yang paling dominan, penelitian ini menganalisis data menggunakan metode relative importance index (RII) dan confidence interval. Hasil penelitian menunjukkan bahwa faktor kebiasaan dalam penyediaan jasa dan lemahnya komunikasi menjadi hambatan utama dalam implementasi e-procurement di Dinas terkait. Guna meminimalkan dampak kedua faktor tersebut, dibutuhkan peningkatan kapasitas sumber daya manusia yang terlibat, disertai pengembangan sarana, prasarana, dan infrastruktur teknologi yang lebih memadai guna mendukung keberlanjutan sistem e-procurement.